Geological setting of basaltic rocks in an accretionary complex, Khangai–Khentei Belt, Mongolia. (22nd May 2013) - Tsukada, Kazuhiro; Nakane, Yuki; Yamamoto, Koshi; Kurihara, Toshiyuki; Otoh, Shigeru; Kashiwagi, Kenji; Chuluun, Minjin; Gonchigdorj, Sersmaa; Nuramkhaan, Manchuk; Niwa, Masakazu; Tokiwa, Tetsuya
Abstract We describe the mode of occurrence and geochemical characteristics of basalts, in the Khangai–Khentei belt in Mongolia, overlain by Middle Paleozoic radiolarian chert in an extensive accretionary complex. These basalts are greatly enriched in K, Ti, Fe, P, Rb, Ba, Th, and Nb in comparison to the composition of the mid‐ocean ridge basalts, indicative of within‐plate alkaline type. Ti/Y vs Nb/Y and MnO/TiO2/P2O5 ratios of the basalts also suggest within‐plate affinities. Considering the geochemical characteristics as well as the conformable relationship with the overlying radiolarian chert, the alkaline basalts were clearly not continental but formed a pelagic oceanic island. The mode of occurrence and geochemistry of the basalts show that the alkaline basaltic volcanic activity had taken place to form an oceanic island in the Paleozoic pelagic region sufficiently far from continents to allow radiolarian ooze accumulation.